The Legal Aspects of Diversity in Academic Pathology - Timothy Craig Allen MD, JD (Elsevier, 2018)
Diversity and inclusion in academic pathology center on building a diverse, inclusive pathology faculty. Understanding the basics of federal law, and the US Supreme Court cases that interpret those laws, allows one to consider good practices in diversity hire recruitment and retention that protects the pathology chair, the pathology department, and the institution. Consideration of inclusion and unconscious bias are helpful in building and sustaining robust, valuable academic pathology faculty diversity.